Car driver attitude towards road safety measures - Yahia, Hussin A.M; Safinia, Sina; Al Musharfi, Noof Khamis; Ali, Saband S.I.A. (Penerbit Universiti Kebangsaan Malaysia, 2017)
Road traffic accidents (RTA) constituted a severe public problem in all countries of the world. Roughly about 1.5 million people around the world die in traffic-related accidents. Its absolute impact is exacerbated by the fact that RTA have become the leading cause of death, especially among young adults who constitute the most economically productive age groups of the larger society. Road traffic accidents also prove to be an issue of economic and social. More than 70% of the injuries and victims of accidents were in low and middle-income countries. The integral role of knowledge and practice of road safety measures necessitate further emphasis in the RTA prevention. The present study seeks to evaluate the road safety measures’ knowledge among car drivers in Tripoli-Libya. A total of 389 drivers had taken in this study. A questionnaire was used to gather some relevant information from the participants. The data collected was run in analysis using SPSS version 19. From the 389 drivers, 310 (79.7%) were male and 79 (20.3%) female. The study results have shown that gender differences in attitudes towards traffic law indicate that there is no significant difference between both sexes. Female had a marginally higher awareness than males with regard to certain substantial issues such as eating, drinking or smoking while driving and using cassette / radio or using the telephone while driving were particularly significant ( P-value = 0.04). Explanations and results of the behaviors of the drivers about safety measures on the roads are discussed.